Waste policy reforms in developing countries: A comparative study of India and Brazil. Issue 9 (September 2020) - Pereira, Alexandre; Ribeiro, Flávio de Miranda; Jeffrey, Robin; Doron, Assa
Over the last decade India and Brazil implemented waste policy reforms to tackle the constraints of their waste management. This study compares those reforms using the methodological framework proposed by Wilson where waste policy evolves through a series of subsequent stages, depending on two aspects: local circumstances; and stakeholders' groups. The current research is exploratory in its scope, adopting this method to describe, compare and evaluate both Indian and Brazilian cases, and also verifying how the model performs when applied to developing countries. The paper confirms Wilson's conclusions, and adds a perception that in developing economies a special local circumstance is to be considered the point of departure, that is, the particular starting point of Wilson's evolution. In addition, the research concludes that participation of diverse stakeholder groups throughout the political process is fundamental, and could be key to overcoming the risks of policy setbacks.